2009
DOI: 10.1080/15226510902767130
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Various Plant Species to Prevent Leakage of N, P, and Metals from Sewage Sludge

Abstract: The preventive effect of vegetation on nutrient and metal leakage from sewage sludge (SS) used in treatment of mine waste was investigated. In a 10-week greenhouse study, the release of ammonium, nitrate, phosphate, Cd, Cu, and Zn from SS was analyzed in the absence (control) and presence of basket willow, fireweed, reed Canary grass (RCG), and Scots pine. Plants significantly decreased the leakage by reducing the amount of leachate, and lowered the concentrations of phosphate (to 0.1 mg L(-1)), Cu (0.8 mg L(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Nevertheless, it has been shown that the spreading of wastewater from diverse origins induced an increase in phosphate levels and in the activity of alkaline phosphatase (not in the activity of acid phosphatase) in plantations of willow and poplar [134,153,168,174]. In contrast, in response to a spreading of limed or anaerobically digested sludge, orthophosphates as well as total phosphates were weakly leached and in a similar way as compared to a conventional phosphorous fertilization [175].…”
Section: Soil and Water Contaminationmentioning
confidence: 73%
See 1 more Smart Citation
“…Nevertheless, it has been shown that the spreading of wastewater from diverse origins induced an increase in phosphate levels and in the activity of alkaline phosphatase (not in the activity of acid phosphatase) in plantations of willow and poplar [134,153,168,174]. In contrast, in response to a spreading of limed or anaerobically digested sludge, orthophosphates as well as total phosphates were weakly leached and in a similar way as compared to a conventional phosphorous fertilization [175].…”
Section: Soil and Water Contaminationmentioning
confidence: 73%
“…In the case of pig manure application in SRC, increases in nitrate (and ammonium) levels were visible from the first months after spreading, while in the case of paper mill sludge application, the effect was visible at the end of the growing season only [170]. Compared with herbaceous species (including reed canary grass), willow used primarily the ammonium present in the sludge and thus was less effective in preventing the risk of nitrate leakage [153]. This is, however, inconsistent with the observations in Ref.…”
Section: Soil and Water Contaminationmentioning
confidence: 84%
“…Plant uptake of ammonium and other cations can cause pH to decrease in the rhizosphere due to excretion of hydrogen ions (Whitehead, ). However, reed canary grass does not prefer ammonium over nitrate (Neüschutz & Greger, ), and nitrate uptake counteracts acidification by excretion of OH‐ions. Thus, in our experiment, pH was only slightly lowered, from 5.9 to 5.7–5.8, in the RCG ash and control treatment, while in the mixed ash treatment the Ca in the ash buffered the soil pH and prevented a decrease in pH.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Searsia lancea to a certain degree could serve as an appropriate woody plant species for phytoremediation purposes since it is able to decontaminate heavy metal polluted soils. However, little is known about the heavy metal tolerance of Searsia lancea compared to existing knowledge on heavy metal resistance and/or tolerance as well as heavy metal uptake and translocation by "typical" remediation woody plant genera like Salix and Populus (e.g., Punshon and Dickinson 1999;Kuzovkina, Knee, and Quigley 2004;Zalesny and Bauer 2007;Neuschütz and Greger 2010).…”
Section: Correlation Of Leaf Analysis Data Photosynthetic Vitality mentioning
confidence: 98%